2021
DOI: 10.1002/jgc4.1470
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to telegenetics in the COVID‐19 era: Patient satisfaction with remote genetic counseling in adult neurology

Abstract: The COVID‐19 pandemic rapidly changed genetic counseling services across the United States. At the University of Pennsylvania (UPenn), a large academic hospital in an urban setting, nearly all genetic counseling (GC) visits for adult–onset disorders within the Department of Neurology were conducted via secure videoconferencing (telegenetics) or telephone between March and December 2020. Although telemedicine services have been steadily emerging, many clinical programs, including the neurogenetics program at UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…These experiences mirror the transition to telehealth genetic counseling more generally during the pandemic (Mills et al, 2021) and align with prior work showing that telehealth genetic counseling increases efficiencies but may also be difficult for some patients to access (Danylchuk et al, 2021;Gorrie et al, 2021). For example, in one survey study, patients reported that virtual genetic counseling visits were generally satisfactory, but a majority of those surveyed still preferred a hybrid telehealth/inperson approach moving forward (Dratch et al, 2021) procedures was one approach that many projects identified as helpful.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These experiences mirror the transition to telehealth genetic counseling more generally during the pandemic (Mills et al, 2021) and align with prior work showing that telehealth genetic counseling increases efficiencies but may also be difficult for some patients to access (Danylchuk et al, 2021;Gorrie et al, 2021). For example, in one survey study, patients reported that virtual genetic counseling visits were generally satisfactory, but a majority of those surveyed still preferred a hybrid telehealth/inperson approach moving forward (Dratch et al, 2021) procedures was one approach that many projects identified as helpful.…”
Section: Discussionsupporting
confidence: 71%
“…These experiences mirror the transition to telehealth genetic counseling more generally during the COVID pandemic (Mills et al, 2021 ) and align with prior work showing that telehealth genetic counseling increases efficiencies but may also be difficult for some patients to access (Danylchuk et al, 2021 ; Gorrie et al, 2021 ). For example, in one survey study, patients reported that virtual genetic counseling visits were generally satisfactory, but a majority of those surveyed still preferred a hybrid telehealth/in‐person approach moving forward (Dratch et al, 2021 ). The experiences of CSER, considered alongside the broader genetic counseling literature, suggest that teleresearch procedures can be valuable tools to facilitate access to clinical genomics research and minimize disruption in case of emergencies that prevent participants from accessing clinical sites in person, research team members from working in an office setting, or both.…”
Section: Discussionmentioning
confidence: 99%
“…25 This testing involves evaluation of a blood specimen and therefore requires infrastructure support to coordinate blood collection, which may be challenging in the COVID-19 pandemic and postpandemic era since much of genetic evaluation has shifted to virtual visits with remote saliva sample collection for GT. 26,27 Mobile phlebotomy and other types of care processes will likely need to be considered more diligently in diverse populations when addressing implementation of RNA testing. 27 In addition, expanded panel testing may be needed to systematically test a larger set of genes among AA men to identify and characterize variants in genes of high or moderate penetrance given that multiple studies have now shown that AA men have a narrow spectrum of germline variants from standard multigene panels.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the expansion of teleconsultation services, travel distance ceased to exist, and the cost and time spent travelling decreased. Consequently, patients faced fewer barriers to having the most appropriate and comfortable GC (Cohen et al 2019 ; Dratch et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of the telephone model offers additional schedule flexibility, reduces geographical barriers, and sometimes is more convenient for the patients. Studies show that patients are very receptive to the telephone model since it offers greater convenience and access to specialised services and multidisciplinary care, minimises economic cost and time related to the consultations, and promotes a feeling of greater perceived personal control (Cohen et al 2016 ; Dratch et al 2021 ). Indeed, questions regarding the use of teleconsultations, patient comfort, time management, and understanding of what was discussed had a high percentage of agreement, showing great acceptance of this model even though most patients had already had a first face-to-face consultation before the pandemic.…”
Section: Discussionmentioning
confidence: 99%